INVESTMENT DECISION, RISK INVESTMENT, AND STOCK RETURN ON STOCK PURCHASE DECISION AT MILLENIAL GENERATION IN SURABAYA - Raditya Yuniar Alfani Pratama; Titin Wahyuni; Tri Ratnawati; Hwihanus (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research was conducted on the Millennial generation in Surabaya. This study was motivated by the aim to test and find out Investment Decision, Risk Investment, And Stock Return On Stock Purchase Decision at Millennial Generation in Surabaya. The sample in this study is the Millennial Generation in Surabaya. This research method uses quantitative. The sample size is 39 with an unknown population. Testing is done using Smart-PLS with outer model test analysis and inner model test. The results showed that Investment Decision has a significant influence on Investment Behavior and Investment Decision has an influence on Stock Purchase Decision. Other variable relationships show insignificant results on Stock Purchase Decision.